Lecturers’ Feedback as a Tool of Power: A Critical Discourse Analysis of Lecturer Feedback in Classrooms - Riefki Fajar Ganda Wiguna; Safrina Arifiani Felayati (Indonesian Journal of English Language Studies (IJELS), 2025)
The types of conversations we hold or avoid with students determine the relationship that we design in our class. Lecturer feedback plays a central role in shaping the learning process, but it also functions as a site where power dynamics are enacted. This paper explores the power relations embedded in language used in lecturer feedback through the lens of critical discourse analysis (CDA). By analyzing how feedback positions students and constructs their identities, this study seeks to uncover the implicit hierarchies and authority structures present in the classroom discourse of the English Literature Study Program Class. The analysis relies on five power bases: referent, reward, expert, legitimate, and coercive. The data were collected by observing six classroom sessions during this time, and feedback instances were transcribed and compiled. In total, approximately 30 feedback examples were selected for in-depth analysis. These include both oral and written feedback that was considered representative of recurring discursive features. The finding shows that lecturer feedback not only reflects power dynamics but also influences the construction of student identity. Furthermore, the feedback that the lecturer provided negatively impacted the learning behavior due to overusing antisocial-based language, which included legitimate and coercive feedback. This feedback also built the students’ identity as incapable learners.